Peruvian and Spanish women using drugs: A study under the gender perspective - Rojas Valero, Milton (2002)
This article examines two different realities concerning the use of drugs under the gender perspective.Epidemiological information and sorne patterns of use are analyzed establishing differences and similarities. The objecti ve is to show the di versity behind the concept <<women indrug consumption>>, a phenomena that affects nationalities, social classes and other social issues. In the case of Peru we analyze data gathered through epidemiological surveys, studies ofuse-dependence and of people contacted throughout the Lugar de Escucha service (telephoneline for drug addicts) in Lima. In Spain, we analyze two sources: the epidemiological studies made at national level and a research about women using chemical drugs.